Struktur Kepemilikan dalam Bingkai Teori Keagenan - Slamet Haryono (Jurnal Akuntansi dan Bisnis, 2005)
Assymetry information or agency problems have been focused by accounting researcher in the last three decades. Considerable efforts have been made by accounting researchers to investigate reason and impilcation in bussiness includes in the stock prices. This study seeks to shed light on this issue and related to ownership stucture, The pattern of manager behaviour. Two aspects of information asymmetry between investors and management are identified and proxied in this study: (1) the availability of information, and (2) the willingness, resources, and ability to process the available information.